Anthology [compact disc] - Hanna, Jeff; Fadden, Jimmie; Ibbotson, Jimmy; Carpenter, Bob (Folk musician); McEuen, John, 1945-; Thompson, Les (Musician); Kunkel, Bruce; Barr, Ralph; Martin, Jimmy; Watson, Doc; Acuff, Roy; Carter, Maybelle, 1909-1978; et al. (Capitol Records, 2017)
In celebration of the band's 50th anniversary, this two CD collection features 37 tracks of Nitty Gritty Dirt Band's discography, hand-picked by the band.